2010
DOI: 10.1007/978-1-4020-5271-2
|View full text |Cite
|
Sign up to set email alerts
|

The Pedagogy of Physical Science

Abstract: The book series Contemporary Trends and Issues in Science Education provides a forum for innovative trends and issues connected to science education. Scholarship that focuses on advancing new visions, understanding, and is at the forefront of the field is found in this series. Accordingly, authoritative works based on empirical research and writings from disciplines external to science education, including historical, philosophical, psychological and sociological traditions, are represented here.For other titl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
0

Year Published

2010
2010
2020
2020

Publication Types

Select...
3
3
1

Relationship

3
4

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 0 publications
0
25
0
Order By: Relevance
“…The awareness of problematics in science education, especially physics, for example, encourages changes in learning pedagogy [6]. The learner's lack of 'pedagogy' now drives a radical change, a process parallel to the 'paradigm shift' in science.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…The awareness of problematics in science education, especially physics, for example, encourages changes in learning pedagogy [6]. The learner's lack of 'pedagogy' now drives a radical change, a process parallel to the 'paradigm shift' in science.…”
Section: Proposed Methodsmentioning
confidence: 99%
“…This approach resonates with sociocultural views of learning where the discourse of science is generated in dialogue between teacher and students and within and across student peer groups (Leach & Scott, ; Mercer, Dawes, Wegerif, & Sams, ). Our previous work on developing science SMK with student‐teachers found that “problematizing” scientific ideas by exploring the difficulties they present for learners enables self‐reflection and promotes discussion of learning, understandings, uncertainties, questions, and interpretations (Heywood & Parker, ). The range of interpretations generated within peer group and tutor discussion provides a positive resource in enhancing criticality and engagement.…”
Section: Methodology and Methodsmentioning
confidence: 99%
“…A large research literature attests to the challenge for learners presented by the subject of “forces” (e.g., Brown & Clement, ; Driver, Squires, Rushworth, & Wood‐Robinson, ; Duit, ; Kruger, Summers, & Palacio, ; Tao & Gunstone, ). In contrast to viewing student‐teachers’ understanding of forces as a deficit of SMK, our previous research demonstrates that by engaging them in understanding how and why forces are problematic in their own learning, they begin to generate both general and science‐related pedagogical knowledge (Heywood & Parker, ). This process of metacognition generally involves two components: the first concerns conscious thinking about cognition and the second control or regulation of thinking that emerges as a direct consequence of raising the awareness of the nature of learning.…”
Section: Introductionmentioning
confidence: 90%
See 1 more Smart Citation
“…Parker & Heywood, 1998;Heywood & Parker, 2010). Students were asked to explore in discussion, by drawing, and then by acting out, how they imagined night and day, or the seasons, being explained by planetary movements.…”
Section: Planetary Movementsmentioning
confidence: 99%